2018
DOI: 10.1021/acsinfecdis.8b00163
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Urine Biomarker Lateral Flow Immunoassay for Monitoring Active Onchocerciasis

Abstract: The parasitic disease onchocerciasis is the second leading cause of preventable blindness, afflicting more than 18 million people worldwide. Despite an available treatment, ivermectin, and control efforts by the World Health Organization, onchocerciasis remains a burden in many regions. With an estimated 120 million people living in areas at risk of infection, efforts are now shifting from prevention to surveillance and elimination. The lack of a robust, point-of-care diagnostic for an active Onchocerca infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 34 publications
0
29
0
Order By: Relevance
“…Indeed, the urinary NATOG concentrations and skin mf densities in the study by Lagatie et al were similar to those observed in our study participants after ivermectin treatment (Table 6). Recently, a lateral flow immunoassay (LFIA) test was developed to detect urinary NATOG [19]. In a small study, this test accurately diagnosed 23 (85%) of the 27 African samples tested, with a cut-off concentration set at 25 µM [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the urinary NATOG concentrations and skin mf densities in the study by Lagatie et al were similar to those observed in our study participants after ivermectin treatment (Table 6). Recently, a lateral flow immunoassay (LFIA) test was developed to detect urinary NATOG [19]. In a small study, this test accurately diagnosed 23 (85%) of the 27 African samples tested, with a cut-off concentration set at 25 µM [19].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a lateral flow immunoassay (LFIA) test was developed to detect urinary NATOG [19]. In a small study, this test accurately diagnosed 23 (85%) of the 27 African samples tested, with a cut-off concentration set at 25 µM [19]. However, the authors of the above-mentioned study did not provide detailed information about mf densities.…”
Section: Discussionmentioning
confidence: 99%
“…There are several options available for the diagnosis of onchocerciasis, principally the diethylcarbamazine (DEC) patch test, skin snip histopathology, DNA detection by polymerase chain reaction (PCR), and antibody assays . As emphasis shifts from prevention to surveillance and elimination in endemic areas and for detection of occasional patients in Europe and North America, a reliable, inexpensive noninvasive method to diagnosis active infections despite a history of prior ivermectin use is pivotal.…”
Section: Diagnosismentioning
confidence: 99%
“…Molecular tools such as real‐time PCR have high diagnostic sensitivity and specificity, as well as high cost. A promising noninvasive urine biomarker immunoassay for diagnosing active onchocerciasis, representing the least invasive technology, has been developed . The use of rapid‐format antibody card test has also demonstrated promise as an alternative to skin snips for use in diagnostic confirmation of onchocerciasis.…”
Section: Diagnosismentioning
confidence: 99%
“…13,14 Urine samples are the end-point of human metabolism and especially interesting as it is an ideal source for the discovery of non-invasive biomarkers that can be readily translated into diagnostic tools. [15][16][17][18][19][20][21] The detection of ketone and aldehyde molecules by liquid chromatography mass spectrometry (LC-MS) remains a challenge due to their poor ionization properties. 22 The development of chemical biology tools in this newly developed research field is limited in comparison with other well-established 'omics' fields.…”
Section: Introductionmentioning
confidence: 99%